2010
DOI: 10.1021/cm100220g
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Hydrothermal Synthesis of Cryptomelane-Type Octahedral Molecular Sieves (OMS-2) and Their Catalytic Studies

Abstract: Manganese oxide octahedral molecular sieves (OMS) are important materials in environmental chemistry, electrochemistry, and heterogeneous catalysis. Here, a rapid process to prepare cryptomelane-type octahedral molecular sieve (OMS-2) nanomaterials using a microwave assisted hydrothermal technique (MW-HT) is presented. With the assistance of microwaves in the hydrothermal reaction, the preparation time of OMS-2 can be as short as 10 s; up to 4 days are required in a conventional hydrothermal reaction. Direct o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 32 publications
7
69
0
Order By: Relevance
“…These phenomenon may imply that the oxygen from pyrolusite lattice is first consumed for catalytic oxidation but late needs to be replenished by molecular oxygen, which have been known as Mars van Krevelen mechanism [36]. Huang et al [11] and Iyer et al [37] have demonstrated that high selectively catalytic oxidation of organic matter on the manganese oxide surface could be attributed to the participation of oxide lattice oxygen into the reaction. In both layered and tunneled manganese oxides, the lattice oxygen or surface hydroxyl groups form excited oxygen species because of electron transfer in the manganese oxide structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenomenon may imply that the oxygen from pyrolusite lattice is first consumed for catalytic oxidation but late needs to be replenished by molecular oxygen, which have been known as Mars van Krevelen mechanism [36]. Huang et al [11] and Iyer et al [37] have demonstrated that high selectively catalytic oxidation of organic matter on the manganese oxide surface could be attributed to the participation of oxide lattice oxygen into the reaction. In both layered and tunneled manganese oxides, the lattice oxygen or surface hydroxyl groups form excited oxygen species because of electron transfer in the manganese oxide structure.…”
Section: Discussionmentioning
confidence: 99%
“…Arising from a high surface charge density, layered manganese oxides, such as birnessite, have been widely used as a typical adsorbent/catalyst/oxidant for removing organic and inorganic pollutants [9] and being most identifiable in soils and sediment [10]. Recently, because of the distinct properties of molecular sieve and reaction selectivity in tunneled manganese oxide, there has been considerable interest in using these materials in wideranging sectors including catalysis, sensing, electronics and photoelectronics [11,12]. However, the study of tunneled manganese oxides application onto pollutants control is still lack in literatures.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] Single-crystalline K 0.25 Mn 2 O 4 could be suitable as a cathode material for lithium ion batteries because its potassium ions can not only maintain the structure, but also increase the ion diffusion rate. [26][27][28][29][30] Solution B was prepared by dissolving 1.5 g of oxone in 10 mL of double de-ionized water.…”
Section: Introductionmentioning
confidence: 99%
“…Cryptomelane, the 2  2 tunnel structured manganese oxide, including octahedral molecular sieve (OMS) and α-MnO 2 , is the most useful and has been most widely studied. OMS with a stoichiometric formula of KMn 8 O 16 Á nH 2 O (often named as OMS-2) has a pore size of 0.46 nm  0.46 nm and can accommodate some other metal cations such as Cu 2 þ , Ni 2 þ , Co 2 þ , Fe 3 þ or V 5 þ to stabilize its framework and tune its electrochemical performance, photosensitivity and catalytic activities [10,11]. Besides, potassium ions and water molecules often exist in the tunnels to provide charge balance and structure stabilization [12].…”
Section: Introductionmentioning
confidence: 99%